(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the aesthetic content of education clusters, the philosophical essence of the principles of aesthetic education, and the considerations related to the regulation of the relations of individuals and society by the aesthetic principles of education clusters are scientifically described.